2015
DOI: 10.4194/1303-2712-v15_3_08
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Alburnus istanbulensis (Battalgil, 1941) is a commercially valuable endemic species which exists in the coastal streams of Marmara Region's northern sectors. 317 individuals, which were collected from Darlık Dam, were examined during December 2011-December 2012. The highest GSI values were 13.07±1.63 for females and 6.95±1.28 for males in the beginning of June. The lowest GSI values were observed in August for females (1±0.33) and in September for males (1.05±0.21). By comparing the histological findings with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…The observed phenomena were similar to previous research on other cyprinid species (Choi et al 2014;Hamzaoglu et al 2015;Krivokapic 2015;Kim et al 2017). In addition, those reported that all oogenesis stages were observed over the year.…”
Section: Relative Proportion Of Oogenesis Stagessupporting
confidence: 92%
See 2 more Smart Citations
“…The observed phenomena were similar to previous research on other cyprinid species (Choi et al 2014;Hamzaoglu et al 2015;Krivokapic 2015;Kim et al 2017). In addition, those reported that all oogenesis stages were observed over the year.…”
Section: Relative Proportion Of Oogenesis Stagessupporting
confidence: 92%
“…The difference between the present research and Hamzaoglu et al (2015) was also observed. The present research found that oocytes were dominant in September (Figure 6), while Hamzaoglu et al (2015) reported that oocytes of Alburnus istanbulensis (Cyprinidae) were dominant in mid-June. The differences were reasonable because the present research used S. orphoides, while Hamzaoglu et al (2015) used A. istanbulensis.…”
Section: Relative Proportion Of Oogenesis Stagescontrasting
confidence: 87%
See 1 more Smart Citation
“…Regarding the GSI values of the species, the GSI values are higher for both sexes in the Darlık Dam (Female: 0.19-16.05; Male: 0.25-8.63) (Hamzaoğlu et al, 2015) than that in this study (Female: 0.36-8.25; Male: 0.06-4.91) for Bayramiç Reservoir specimens. Additionally, the GSI values of the species in the earlier study, which was carried out in the Ömerli Reservoir, ranged from 8.2 to 9.9 between 2002 and 2007 (yearly values) (Tarkan et al, 2012).…”
Section: Parameters Of the Length-weight Relationshipscontrasting
confidence: 75%
“…There have been studies on A. istanbulensis species distribution (Sarı et al, 2006;Özuluğ, 2008;Geiger et al, 2014;Saç & Özuluğ, 2014;Boll et al, 2016;Gaygusuz et al, 2017;Saç & Özuluğ, 2017a,b,c;Sarı et al, 2019;Çiçek et al, 2020), maturity and gonadosomatic index (Tarkan et al, 2005;Tarkan et al, 2012;Hamzaoğlu et al, 2015), parasites (Kırcalar & Soylu, 2014), and feeding characteristics (Yalçın Özdilek & Jones, 2014;Yalçın Özdilek et al, 2019). However, there are limited studies on length-weight relationships and length-weight distributions (Tarkan et al, 2005;Tarkan et al, 2006;Saç & Okgerman, 2016;Gaygusuz et al, 2017;, and age distribution (Başdemir et al, 2010;Çiçek et al, 2015) with A. istanbulensis's former name (C. chalcoides and A. chalcoides).…”
Section: Introductionmentioning
confidence: 99%